2022
DOI: 10.1021/acsami.2c10590
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode-Driven Micromotor Based on Foam-like Carbon Nitride and Fe3O4 with Improved Manipulation and Photocatalytic Performance

Abstract: Micro/nanomotors have emerged as a vibrant research topic in biomedical and environmental fields due to their attractive self-propulsion as well as small-scale functionalities. However, single actuated micro/nanomotors are not adaptive in facing intricate natural and industrial environments. Herein, we propose a new dual-mode-driven micromotor based on foam-like carbon nitride (f-C3N4) with precipitated Fe3O4 nanoparticles, namely, Fe3O4/f-C3N4, powered by chemical/magnetic stimuli for rapid reduction of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…EPR spectra of the JPMP1/JPMP2–H 2 O 2 –DMPO system recorded at different times, with the same conditions, are given in Figure c,d. As shown in these figures, the EPR spectra were composed of quartet signals separated by ∼15 G with relative intensities of 1:2:2:1, which is the characteristic signal of DMPO- • OH spin adduct, proving the generation of • OH . Therefore, the radicals reported by the scavenging experiments are consistent with the types of ROS detected by the EPR study performed for the JPMP1 and JPMP2 systems (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPR spectra of the JPMP1/JPMP2–H 2 O 2 –DMPO system recorded at different times, with the same conditions, are given in Figure c,d. As shown in these figures, the EPR spectra were composed of quartet signals separated by ∼15 G with relative intensities of 1:2:2:1, which is the characteristic signal of DMPO- • OH spin adduct, proving the generation of • OH . Therefore, the radicals reported by the scavenging experiments are consistent with the types of ROS detected by the EPR study performed for the JPMP1 and JPMP2 systems (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of their studies, they proved that the structures showed high catalytic activity under hybrid stimuli of the magnetic field and light to degrade pollutants in an aqueous solution . Foam-like structures Fe 3 O 4 /f-C 3 N 4 were also prepared by Feng et al A study was carried out for the cost-effective reduction of antibiotics in industrial wastewater treatment by increasing the catalytic activity of the structures by the magnetic field and light . Feng et al also reported covalent organic framework-based micro-/nanomotors in another study.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the efforts from many research groups, combined propulsion MNMs were also fabricated for antibacterial applications, 53,54 degradation of pollutants, [116][117][118] and other applications. 119,120 Among them, magnetic/chemical hybrid MNMs have been commonly applied for antibacterial application.…”
Section: Combined Propulsionmentioning
confidence: 99%
“…MCIEX is expected to react to light and H 2 O 2 fuel to produce locomotion. [47,48] Under UV-light gradient, MCIEX exhibits negative phototaxis (Figure 2a,b; Figure S7 and Movie S2, Supporting Information) resulting from the asymmetric distribution of ionic species around MCIEX. Due to the limited penetration depth of UV light, a faster photo-Fenton reaction on the illuminated side results in higher concentrations of OH − and Fe 3+ , while on the shadow side, ion-exchange leads to a higher H + concentration.…”
Section: Light-controlled Reconfiguration Of Mciex Swarmmentioning
confidence: 99%